Working stiff : two years, 262 bodies, and the making of a medical examiner - Melinek, Judy (Scribner, 2014)
"The fearless memoir of a young forensic pathologist's "rookie season" as a NYC medical examiner, and the cases--hair-raising and heartbreaking and impossibly complex--that shaped her as both a physician and a mother. Just two months before the September 11 terrorist attacks, Dr. Judy Melinek began her training as a New York City forensic pathologist. With her husband T.J. and their toddler Daniel holding down the home front, Judy threw herself into the fascinating world of death investigation--performing autopsies, investigating death scenes, counseling grieving relatives. Working Stiff chronicles Judy's two years of training, taking readers behind the police tape of some of the most harrowing deaths in the Big Apple, including a firsthand account of the events of September 11, the subsequent anthrax bio-terrorism attack, and the disastrous crash of American Airlines flight 587. Lively, action-packed, and loaded with mordant wit, Working Stiff offers a firsthand account of daily life in one of America's most arduous professions, and the unexpected challenges of shuttling between the domains of the living and the dead. The body never lies--and through the murders, accidents, and suicides that land on her table, Dr. Melinek lays bare the truth behind the glamorized depictions of autopsy work on shows like CSI and Law & Order to reveal the secret story of the real morgue"--